A grand musical Academy at the Kärntnerthortheater in Vienna, April 3, 1781 (Vienna; Austria, 2020)
Reproduction of a handbill for a program at the Kärntnerthortheater in Vienna featuring a Mozart Symphony and the composer at the piano in a solo performance, April 3, 1781. Also on the program was the musical drama Die Pilgrime aus Golgatha by Friedrich Wilhelm Zachariä set to music by Johann Georg Albrechtsberger.